Penerapan Prinsip Berkelanjutan Pada Bangunan Nipah Mall Di Makassar - Ichwan Isalmi Amir,; M. Alfiansayah,; Andhy Masardy Tahir,; Nuryuningsih, Nuryuningsih (TIMPALAJA : Architecture Student Journals, 2022)
Abstract_ New shopping center facilities in urban areas are competing to be established by managers and investors to reap the benefits of the increasing demand for today's daily needs. However, the aspects applied to the building have not fully paid attention to sustainable architectural factors, so they negatively impact the surrounding environment. The Nipah Mall building was chosen because it is an example of a shopping center facility in demand by the public with reasonably rapid growth in every city, including Makassar today. As for this research, the qualitative method is collecting data, searching the literature, conducting field observations, and analyzing the principles of sustainable architecture that have been applied to case studies. This research is expected to increase knowledge related to shopping center building standards and the application of the appropriate sustainable architectural concept in it.